DETERMINANTS OF MSME COMPETITIVENESS IN ACEH PROVINCE - Akhyar, Chairil; Ikramuddin, Ikramuddin; Yusuf Iis, Em.; Mariyudi, Mariyudi (RADJA PUBLIKA, 2021)
Micro, Small and Medium Enterprises are one of the drivers of national economic growth, because of their ability to absorb workers equal to 95% with a total investment of 60.4%. This study aims to examine the effect of capital capability, empowerment, and product innovation on the competitiveness of micro, small and medium enterprises. And the role of product innovation as a mediating variable in the indirect influence between the coaching program and capital on the competitiveness of micro, small and medium enterprises in Aceh. Study designs a Quantitative Research. This research was conducted on micro, small and medium enterprises (MSMEs) in Aceh Province, Indonesia. The population in this study were micro, small and medium enterprises (MSMEs). The research sample was determined by purposive sampling, with a sample size of 272 SMEs. While the data analysis tool usesStructural Equation Modeling (SEM) Amos to test the effect between exogenous variables and endogenous variables. Pdirect effect test found that capital has no effect on product innovation by -0.035, P-Value 0.754 (Not supported H1). Empowerment has a significant effect on product innovation by 0.249, p-value 0.030 (Supported H2). Capital has a significant effect on the competitiveness of SMEs by 0.220, p-vale 0.014 (Supported H3). Empowerment has a significant effect on MSME competitiveness by 0.542, and p-value 0.000 (Supported H4), and product innovation has a significant effect on MSME competitiveness by 0.274 and p-value 0.000 (supported H5). To test the indirect effect using the Sobel test calculator, it was found that product innovation variables were able to partially mediate the relationship between capital and empowerment on the competitiveness of SMEs. The results of the study indicate that the Empowerment and Product Innovation variables have a significant effect on the competitiveness of MSMEs both directly and indirectly, except for the Capital variable which is found to be insignificant to Product Innovation. Finally, the researcher concludes that the competitiveness of micro, small and medium enterprises in Aceh is determined by the factors of capital capability, empowerment program and product innovation.